Cognitive enhancement: Effects of methylphenidate, modafinil, and caffeine on latent memory and resting state functional connectivity in healthy adults. Issue 14 (7th June 2022) - Becker, Maxi; Repantis, Dimitris; Dresler, Martin; Kühn, Simone
Abstract: Stimulants like methylphenidate, modafinil, and caffeine have repeatedly shown to enhance cognitive processes such as attention and memory. However, brain‐functional mechanisms underlying such cognitive enhancing effects of stimulants are still poorly characterized. Here, we utilized behavioral and resting‐state fMRI data from a double‐blind randomized placebocontrolled study of methylphenidate, modafinil, and caffeine in 48 healthy male adults. The results show that performance in different memory tasks is enhanced, and functional connectivity (FC) specifically between the frontoparietal network (FPN) and default mode network (DMN) is modulated by the stimulants in comparison to placebo. Decreased negative connectivity between right prefrontal and medial parietal but also between medial temporal lobe and visual brain regions predicted stimulant‐induced latent memory enhancement. We discuss dopamine's role in attention and memory as well as its ability to modulate FC between large‐scale neural networks (e.g., FPN and DMN) as a potential cognitive enhancement mechanism. Abstract : In this study, we investigated the effects of stimulants like methylphenidate, modafinil, and caffeine on latent memory and functional connectivity in a double‐blind randomized placebo controlled study in 48 healthy male adults. Our results show that performance in different memory tasks is enhanced, and functional connectivity specifically between the fronto‐parietal and default mode network is modulated by the stimulants in comparison to placebo. Decreased negative connectivity between right prefrontal and medial parietal but also between medial temporal lobe and visual brain regions predicted stimulant‐induced latent memory enhancement.